RANCANG BANGUN SISTEM MONITORING AREA PACKAGING DI PT GARAM (PERSERO) BERBASIS OUTSEAL - HAIWELL - Wafa, Daimul; Denny Irawan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Technological developments in this increasingly rapid modern era are widely used in various sectors, one of which is in the industrial sector. In the industrial era 4.0, of course, the development of industrial automation will be very much needed in an industry. This development clearly aims to ensure the quality of production results, reduce production downtime and reduce human labor costs so that the production process is faster and more efficient. In this thesis proposal, a method for designing and making a monitoring system prototype in the packaging area of industrial salt production is written using Outseal PLC and Haiwell HMI. The work process in this system is monitoring work in the packaging area and processing production recaps. All of these systems were processed using the Outseal Nano V 5.2 PLC and programmed in the Outseal Studio software and displayed by HMI Haiwell. The results of the monitoring system implementation are aims to help for operator and staff to exercise control over the packaging area and increase efficiency in the industrial salt factory area.